"It's Worth It in the End": Veterans' Experiences in Prolonged Exposure and Cognitive Processing Therapy. Issue 1 (February 2017) - Hundt, Natalie E.; Barrera, Terri L.; Arney, Jennifer; Stanley, Melinda A.
Abstract: Despite the efficacy of evidence-based psychotherapies (EBP) for posttraumatic stress disorder (PTSD) and efforts to disseminate them, only 6–13% of veterans seeking care through the Veterans Affairs health care system receive these treatments. EBPs such as prolonged exposure (PE) and cognitive processing therapy (CPT) are exposure-based treatments. Provider and patient fears regarding the tolerability of exposure-based treatments likely impede their delivery and completion. The present study utilized qualitative interviews with 23 veterans who completed at least eight sessions of either PE or CPT to elicit firsthand accounts of veterans' experiences in these EBPs. Results suggest that while a minority of veterans reported initial symptom worsening, the majority of veterans reported positive experiences and felt that, despite being stressful, these EBPs were "worth it." Most veterans discussed thoughts of discontinuing treatment prematurely, but stated that adherence was encouraged by their commitment to finishing, desperation for relief, therapist/group support, and family support. Veterans believed exposure made an important contribution to symptom improvement, as did greater self-understanding and changing negative or unhelpful beliefs. These findings indicate veteran satisfaction with PE and CPT, and may assist providers to develop strategies to increase adherence and treatment completion. Highlights: Veterans' experiences in cognitive-behavioral PTSD therapies are examined. Many veterans with PTSD consider dropping out of treatment. Veterans discuss factors that contribute to treatment adherence. Veterans report that the treatments were "worth it" despite stressfulness.